SUPPLEMENTATION EFFECTS OF TANNIN AND SAPONIN EXTRACTS TO DIETS WITH DIFFERENT FORAGE TO CONCENTRATE RATIO ON In vitro RUMEN FERMENTATION AND METHANOGENESIS - Yogianto, Y.; Sudarman, A.; Wina, E.; Jayanegara, A. (Diponegoro University, 2014)
This experiment was aimed to investigate the effect of combining tannin and saponin extracts onruminal methane emission of diets with different proportion of forage to concentrate in the in vitrofermentation. The experiment was conducted in a factorial block design. The first factor was theproportion of forage:concentate in diets (70:30 and 30:70) and the second was addition of tannin andsaponin extracts (control, tannins, saponins, tannins + saponins) in the dose of 2 mg/ml. Variablesobserved were gas production kinetics, methane production, dry matter digestibility (DMD), organicmatter digestibility (OMD) and ammonia concentration. Results revealed that addition of tannins,saponins and their combination generally lowered total gas and methane production during 24 and 48 hof incubation period in both types of diets (P<0.05), but combination of tannins and saponins comparedwith their separated forms did not show any significant differences. The addition of tannins, saponinsand their combination reduced DMD, OMD and ammonia significantly (P<0.05). It can be concludedthat the addition of tannin, saponin and their combination at a dose of 2 mg/ml could reduce methaneemission but followed by a decline in the DMD, OMD and ammonia.